'I put my "police head" on': Coping strategies for working with sexual offending material. (September 2019) - Parkes, Ruth; Graham-Kevan, Nicola; Bryce, Jo
This paper explores the coping strategies of UK police staff who are exposed to sexual offence material (SOM). Eleven police staff completed a questionnaire then took part in semi-structured interviews. Themes were identified using Interpretative Phenomenological Analysis (IPA). This paper explores the theme 'Coping strategies for working directly with material', focusing on the most common strategies employed: 'Detachment', 'Avoidance' and 'Process-driven' approaches. Links between coping and different features of SOM are examined, including victim characteristics and audio content. The impact of organisational factors which make coping strategies more or less effective are also explored, along with potential sources of support.